A United States Catholic Health Care Ethicist reflects on Evangelium Vitae and the Life Challenges Ahead (1995-2005)* - Barnet, Robert (O Mundo da Saúde, 2006)
…The present encyclical [Evangelium Vitae] ..is therefore meant to be a precise and vigorous reaffirmation of the value of human life and its inviolability, and at the same time a pressing appeal addressed to each and every person, in the name of God: respect, protect, love and serve life, every human life! Only in this direction will you find justice, development, true freedom, peace and happiness.